Does economic liberalization increase government accountability? - Rayamajhee, Veeshan; March, Raymond J. (Journal of economic behavior & organization, 2025)
This paper examines the impact of economic liberalization on government accountability. Using a country-level panel spanning 1900-2020 from the V-DEM dataset, we exploit discrete and sustained jumps in state ownership and control of the economy to identify instances of reforms toward economic liberalization. We use a doubly-robust staggered difference-in-differences approach on stacked data and find a sizable and positive relationship between economic liberalization and government accountability. We further identify three channels through which capitalistic reforms improve government accountability: greater media independence and representation, stronger civil society participation, and broader inclusion of diverse elite groups, all of which impose checks on governmental power. Our results are robust to a host of robustness checks including exclusion of different geo-political regions and historical episodes as well as alternative treatment definitions.